Exploring the Experience of Stigma among People Living with HIV in Bali, Indonesia: Qualitative Phenomenological Study - Hidayat, Jufri; Huang, Xuan-Yi; Lin, Hung-Ru; Wei, Shiow-Jing; Chen, Miao-Yen; Pranata, Satriya (UI Scholars Hub, 2022)
Background: Human immunodeficiency virus (HIV)-related stigma continues to be a serious problem for people living with HIV (PLWH). This study aimed to explore stigma experience among PLWH in Bali, Indonesia. Methods: This research was a qualitative descriptive phenomenological study. With the help of a local clinician–researcher and the staff of the United Nations Program on AIDS Commission, Bali, 10 participants were recruited by purposive sampling and participated in semi-structured interviews via WhatsApp online audio from April to December 2021. Data were analyzed using Colaizzi’s process. Results: The following three themes emerged: (1) experiencing discrimination, (2) getting stronger through stigma experiences, and (3) receiving support. Interviews revealed that PLWH in Bali experience stigma and discrimination across settings, including communities, families, friends, employers, and health care. Some participants could turn the pressure of stigma into a source of strength, making them psychologically and mentally strong. This phenomenon mostly happened when the patients had positive attitudes toward illness and good coping mechanisms. Conclusions: This study showed the importance of support from family, friends, and organizations in surviving stigma. For PLWH, having a sense of self-support and resilience and adaptive mechanisms also help ease the negative effects of stigma and discrimination.